A system-level bandwidth design method for wormhole network-on-chip. Issue 11 (1st November 2016) - Wang, Jian; Li, Yubai; Liao, Changjun
ABSTRACT: To improve the Network-on-Chip (NoC) performance, we propose a system-level bandwidth design method customising the bandwidths of the NoC links. In details, we first built a mathematical model to catch the relationship between the NoC commutation latency and the NoC link bandwidth, and then develop a bandwidth allocation algorithm to automatically optimise the bandwidth for each NoC link. The experimental results show that our bandwidth-customising method improves the NoC performance compared to the traditional uniform bandwidth allocation method. Besides, it can also make our NoC to achieve the same communication performance level as the uniform bandwidth NoC but using fewer bandwidth resources, which is beneficial to save the NoC area and power.